Penguatan Identitas Produk melalui Desain Label: Studi Pengabdian pada UMKM Ayam Geprek 'DR' Cikarang - Rismawati .; Renaldi Mahadika; Chintya Shafwa Nabilla; Siti Nurhayati; Muhamad Iqbal (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This community service aims to enhance the understanding and skills of SME entrepreneurs in calculating production costs using the full costing method for ayam geprek businesses located on Jl. Inspeksi Kalimalang, South Cikarang. The full costing method was chosen because it provides a comprehensive overview of production costs, including overhead costs that are often overlooked by SME entrepreneurs. This activity was carried out using a qualitative method through direct interviews with SME entrepreneurs to identify and determine production costs. The results of this community service, with the application of the full costing method, show that the total production cost over one month was IDR 11,700,000, with a cost of goods manufactured (COGM) per portion of IDR 7,446.67, generating a profit margin of 243.03%. In conclusion, this community service activity can make a tangible contribution to improving the management skills of small and medium enterprises in the culinary sector, particularly by optimizing production cost calculations using the full costing method for ayam geprek.